Sex-specific dive characteristics in a sexually size dimorphic duck - Osterrieder, Sylvia; Weston, M.; Robinson, R.; Guay, P. (Wildfowl and Wetlands Trust, 2014)
© Wildfowl & Wetlands TrustDive duration generally increases with body size in animals including wildfowl. Therefore, diving behaviour may vary between the sexes in sexually size dimorphic species, such as the extremely sexually size dimorphic Musk Duck Biziura lobata. However, a previous study reports longer dives in the smaller sex (females) when breeding. In this study, non-breeding male Musk Ducks dived for significantly longer periods than females and tended to have longer inter-dive intervals, conforming to the general patterns described for other species. The differences in dive behaviour we describe may be explained by niche partitioning or differential oxygen requirements or uptake rates by the sexes.